1995
DOI: 10.1038/nsb0695-480
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an inhibitor complex of the proteinase from feline immunodeficiency virus

Abstract: The crystal structure of a recombinant form of the proteinase encoded by the feline immunodeficiency virus (FIV PR) has been solved at 2 A resolution and refined to an R-factor of 0.148. The refined structure includes a peptidomimetic, statine-based inhibitor, LP-149, which is an even more potent inhibitor of HIV PR. Kinetic parameters were obtained for the cleavage of five substrates by FIV PR, and inhibition constants were measured for four inhibitors. The structure of FIV PR resembles other related retrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 29 publications
5
95
0
Order By: Relevance
“…L97 80 is associated with the S1/S2 subsites, and substitutions at this position may influence the preferences at the P1/P2 positions of a substrate (20,28,54). In addition to poor/delayed cleavage at the FIV NC-p2 junction, inefficient processing at the FIV MA-CA cleavage junction by the L97 80 T mutant was also observed (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…L97 80 is associated with the S1/S2 subsites, and substitutions at this position may influence the preferences at the P1/P2 positions of a substrate (20,28,54). In addition to poor/delayed cleavage at the FIV NC-p2 junction, inefficient processing at the FIV MA-CA cleavage junction by the L97 80 T mutant was also observed (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Most of the residues in the active sites of the two PRs are distinct (Fig. 1A, residues around Asp25 in HIV-1 PR and Asp 30 in FIV PR, the flaps, and the " 90s loop"), but the 3-dimensional structures of the two active cores are highly conserved (20,28,54). The structural locations of the substitutions investigated in this study are shown on one monomer of the dimeric FIV and HIV-1 PRs in Fig.…”
Section: Gag Proteins and Gag-pol Polyproteins Of The Two Viruses (Fimentioning
confidence: 99%
“…The structure of this inhibitor complexed with FIV proteinase has been solved and refined to 0.2-nm resolution [20]. Superposition of this complex with that of EIAV [Gly54]proteinase complexed with HBY-793 shows that the P3 naphthyalanine substituents occupy closely similar positions in the two structures.…”
Section: Discussionmentioning
confidence: 99%
“…It was clear that in EIAV PR the variable loops A1 and A2 would be the same as in the HIV-1 enzyme. We expected the insertion of five residues in EIAV PR to be located in the variable region of a wide surface loop, which had been observed to have a very specific conformation in all known structures of the retroviral proteinases Tong et al, 1993;Wlodawer et al, 1995). Because we expected this fragment to have a different conformation in EIAV PR as well, we decided not to model it, and instead kept it as polyalanine with the conformation found in HIV-1 PR, without inserting extra residues.…”
Section: Model Buildingmentioning
confidence: 99%
“…and for the proteinases of other retroviruses [e.g., SIV, Sugrue et al, 1994; feline immunodeficiency virus (FIV), Wlodawer et al, 1995; Rous sarcoma virus (RSV), Jaskolski et al, 19901. and discussion We report here the elucidation of the structure of a single-site I54G mutant form of EIAV PR complexed with the only inhibStructure solution and de.ycrjptjon itor (HBY-793) known to inhibit both the wild-type and mutant EIAV PR, as well as HIV-1 PR, with subnanomolar potency…”
mentioning
confidence: 99%